Fifteen-minute consultation: An approach to the child receiving glucocorticoids. Issue 3 (7th August 2020) - Kanthagnany, Sai-Kalyani; Lane, Laura C; Wood, Claire; Sachdev, Pooja; Drake, Amanda Jane; Cheetham, Timothy
Abstract : Glucocorticoids (GC) are used in paediatric practice for a broad range of conditions and all paediatricians will prescribe GC, in some form, during their career. A wide variety of GC formulations, doses and administration routes are used for periods of time ranging from days to years. Exposure to exogenous GC can result in hypothalamic-pituitary-adrenal axis suppression—otherwise known as adrenal suppression (AS). Patients with AS may be well most of the time but if GC therapy is reduced or stopped or if additional endogenous GC cannot be generated during illness, then an absolute or relative lack of GC can result in severe illness or death. Here, we highlight the relevance of AS to all paediatricians by providing an overview of the background and discussing the presentation and approaches to the management of this clinical entity.